Transition to Green Building Through Retrofitting: Quantitative Analysis of Appropriate Sizing of Lighting, Cooling and Water Consumption Using Parametric Variations in Residential Building - Fawad Azeem; Zulfiqar Memon; Abdullah Ammar (Buildings)
Residential buildings are turning out to be huge power-consumption units that accommodate multiple families. To limit energy consumption and environmental impacts, conventional buildings are being retrofitted as green buildings. However, due to the lack of awareness among residents and construction agencies, the adoption pace of green building retrofitting is slow. Under current retrofitting procedures, the building envelopes have been given great attention, which is an expensive and complex process. However, the sizing of lighting and cooling loads has not been considered in the retrofitting process, and careful attention is needed as they are major building loads. In this research, an appropriate sizing of lighting and cooling loads, along with optimized water consumption, is performed. The sizing is obtained using the parametric variations, i.e., varying the coefficient of utilization (CU) factor of lighting and the wall-to-window ratio (WWR) of different rooms to quantify their impact on power consumption. The optimization of water consumption is performed using particle swarm optimization. A case study of a residential building was taken, and a residential unit was considered in the study. It was found that parametric variations can reduce sizing, which has a significant impact on the overall power consumption, whereas optimizing the water consumption can significantly reduce the utilization of water in the building. Finally, the comparison is made in terms of power consumption for the current practices and the optimal analysis. It was found that with the proposed sizing and subsequent retrofitting, the lighting consumption was reduced to 34%, whereas the space cooling requirements were reduced to 19%.